Anechoic wind tunnel tests on high-speed train bogie aerodynamic noise. Issue 2 (3rd April 2017) - Latorre Iglesias, Eduardo; Thompson, David J.; Smith, Malcolm; Kitagawa, Toshiki; Yamazaki, Nobuhiro
ABSTRACT: Aerodynamic noise becomes a significant noise source at speeds normally reached by high-speed trains. The train bogies are identified as important sources of aerodynamic noise. Due to the difficulty to assess this noise source carrying out field tests, wind tunnel tests offer many advantages. Tests were performed in the large-scale low-noise anechoic wind tunnel at Maibara, Japan, using a 1/7 scale train car and bogie model for a range of flow speeds between 50, 76, 89 and 100 m/s. The dependence of the aerodynamic noise from the bogie region on different factors has been studied for different bogie configurations and inflow conditions representing different positions of the bogie along the train. The speed dependence and the noise directivity have also been assessed. The results show the particular importance of the components exposed to the free flow, whereas those shielded within the bogie cavity are shown to radiate much less noise.